What influences treatment satisfaction in patients with personality disorders? A naturalistic investigation in a hospitalization setting - Stefan Gebhardt; Martin Tobias Huber (Mental Illness)
Treatment satisfaction of different mental disorders is still poorly understood, but of high clinical interest. Inpatients of a general psychiatric care hospital were asked to fill out questionnaires on satisfaction at discharge and clinical variables at admission and discharge were assessed. On the basis of an exploratory approach, differences in treatment satisfaction among diagnostic groups were examined by means of one-way analysis of variance. Potential associated clinical and socio-demographic variables were studied using multi/univariate tests. Patients with personality disorders (n=18) showed a significantly lower treatment satisfaction (ZUF-8, Zurich Satisfaction Questionnaire) and a slightly lower improvement of symptoms (CGI, Clinical Global Impression) and global functioning (GAF, Global Assessment of Functioning scale) than that of other diagnostic groups (n=95). Satisfaction in patients with personality disorders correlated much stronger with the symptom improvement and slightly with the functioning level than in patients without personality disorders. Interestingly, in patients with personality disorders psychopharmacological treatment in general (present versus not present) was independent from satisfaction. This exploratory investigation suggests that a lower satisfaction of patients with personality disorders in a general psychiatric hospital is mainly based on a reduced improvement of the symptoms and of the global functioning level.